Transient Deformation and Stress Patterns Induced by the 2010 Maule Earthquake in the Illapel Segment - Peña, Carlos; Heidbach, Oliver; Moreno, Marcos; Melnick, Daniel; Oncken, Onno (Frontiers in Earth Science, 2021)
Evaluating the transfer of stresses from megathrust earthquakes to adjacent segments is fundamental to assess seismic hazard. Here, we use a 3D forward model as well as GPS and seismic data to investigate the transient deformation and Coulomb Failure Stresses (CFS) changes induced by the 2010 Maule earthquake in its northern segment, where the Mw 8.3 Illapel earthquake occurred in 2015. The 3D model incorporates the coseismically instantaneous, elastic response, and time-dependent afterslip and viscoelastic relaxation processes in the postseismic period. We particularly examine the impact of linear and power-law rheology on the resulting postseismic deformation and CFS changes that may have triggered the Illapel earthquake. At the Illapel hypocenter, our model results in CFS changes of ~0.06 bar due to the coseismic and postseismic deformation, where the coseismic deformation accounts for ~85% of the total CFS changes. This is below the assumed triggering threshold of 0.1 bar and, compared to the annual loading rate of the plate interface, represents a clock advance of approximately only two months. However, we find that sixteen events with Mw≥ 5 in the southern region occurred in regions of CFS changes > 0.1 bar, indicating a potential triggering by the Maule event. Interestingly, while the power-law rheology model increases the positive coseismic CFS changes, the linear rheology reduces them. This is due to the opposite polarity of the postseismic displacements resulting from the rheology model choice. The power-law rheology model generates surface displacements that fit better to the GPS-observed landward displacement pattern.